Wireless Integrated Gait Analysis System for Heel-Strike and Toe-Off Measurement - A. Razak, A. H.; M. Aruwa, M. M.; Al Junid, S. A. M.; M. Idros, M. F.; Halim, A. K.; Haron, N.Z.; Khairuddin, N. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
This paper presents the development of a wireless system for gait analysis. Nowadays, gait analysis becoming an important tool to diagnosis or evaluate certain diseases. It has a lot of improvements since the introduction of biomechanics and gait analysis has to be more precise. A lot of studies had been made to determine the measuring of the gait parameters. However, only a few of them specify the measurement of “heelstrike” and “toe-off” timing parameters. Even though there is a research center providing the stated quantitative information, it has been done in a highly accurate computer laboratory. This super computer method is very expensive and not affordable. While in the medical world, the gait parameters analyzed without any guarantee of the results obtained. Therefore, there is a need of the system that is not only low cost but also can produce a real-time feedback. The main objective of this new insole system is to design and implemented a low cost and wearable solution for “heel-strike” and “toe-off” timing parameters using the Force Sensing Resistor (FSR) sensor. The design of this new insole system consisting of six FSR sensors that will deliver a convenient result in the stated gait parameters and offer an additional function which is the gait symmetry observation. The advantage of this project is that it would be a great achievement in the new gait analysis system by introducing the concept of portable wireless and real time feedback device (self–monitor). In conclusion, the design of this new insole system is predicted to help clinician and researchers to develop a new model of gait analysis system.